Atmospheric and terrigenous metal accumulation over 3000 years in a French mountain catchment: Local vs distal influences. (September 2017) - Hansson, Sophia V.; Claustres, Adrien; Probst, Anne; De Vleeschouwer, François; Baron, Sandrine; Galop, Didier; Mazier, Florence; Le Roux, Gaël
Graphical abstract: Highlights: Pre-industrial Pb and Sb atmospheric contamination is evident in peatlands. Local atmospheric contamination was dominant in 500 BC–AD 600 and AD 1200–1500. Recent deposition reflects long range European trends. Erosion releases previously stored Pb and minerals from AD 1500 to 1900. Remobilization of stored contaminants is connected to pastoralism. Abstract: In this paper we report analyses of four peat cores taken from a mountain valley in the French Pyrenees where ancient metallurgical and agro-pastoral activities have occurred. By combining a range of geochemical and chronological proxies we investigated (1) the importance of PHTE (Potentially Harmful Trace Element) accumulation during pre-industrial times compared to recent accumulation, and (2) the intimate relationship between landscape use and terrestrial PHTE transfers. We show how long human-environment interaction in mountain environments and pre-industrial anthropogenic activities led to PHTE accumulation equal to or even exceeding that of modern times. Atmospheric contamination by PHTE occurred throughout 500 BC − AD 500 for lead (Pb) and antimony (Sb), AD 1200–1600 for only Pb, and the last 150 years for Pb, Sb and copper (Cu) combined. Lead isotopes allowed determination of the impact of Pb contamination from significant local mining and metallurgical activities during the Middle Ages. An estimation of PHTE inventories derived from atmospheric deposition suggests that 85% of Pb accumulation occurred before AD 1800, thus highlighting the influence of past local activities to the accumulation of atmospheric contaminants compared to that of more recent periods. Enhanced erosion input to one of the mires is evident from AD 1600 to 1950, and intensive grazing coupled with forest clearings are the likely cause of these rapid transfers of natural PHTE and previously stored Pb to downstream mires. Remobilized Pb in the impacted peatland represent at least one third of the total Pb-inventory, suggesting that terrestrial transfers were important and acting as hotspot sources of PHTE accumulation.